2004
DOI: 10.1007/s00125-004-1531-3
|View full text |Cite
|
Sign up to set email alerts
|

Improved survival of microencapsulated islets during in vitro culture and enhanced metabolic function following transplantation

Abstract: Aims/hypothesis. The aim of this study was to determine whether a simple alginate capsule can prolong islet survival and function during long-term tissue culture. We also wanted to observe the ability of these encapsulated islets to restore glucose responsiveness to diabetic recipients, along with the quantity of islets required to do so. Methods. We compared the recovery and metabolic function of encapsulated canine islets with that of non-encapsulated canine islets following 1, 2 or 3 weeks of tissue culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 34 publications
1
37
0
1
Order By: Relevance
“…This strategy has provided a wide range of promising therapeutic treatments for central nervous system diseases (Borlongan et al 2004), diabetes (Korbutt et al 2004), hemophilia (Hortelano et al 1996), and anemia (Rinsch et al 2002) among others. This technology offers a safe and manufacturable method for the local and systemic delivery of therapeutic molecules from the enclosed cells.…”
Section: Cell Encapsulationmentioning
confidence: 98%
“…This strategy has provided a wide range of promising therapeutic treatments for central nervous system diseases (Borlongan et al 2004), diabetes (Korbutt et al 2004), hemophilia (Hortelano et al 1996), and anemia (Rinsch et al 2002) among others. This technology offers a safe and manufacturable method for the local and systemic delivery of therapeutic molecules from the enclosed cells.…”
Section: Cell Encapsulationmentioning
confidence: 98%
“…The material for encapsulation can be brown algae derived alginate which is currently being used in clinical trials [ 134 ]. Another material, polysulphone can also be utilized but it needs to be modifi ed in order to reduce insulin adsorption [ 135 ].…”
Section: Remaining Challenges and Clinical Perspectivesmentioning
confidence: 99%
“…Moreover, Korbutt et al [9] have shown that immobilizing islets in alginate beads improves islet cell survival in vitro and in vivo. In the latter case, the improvement was not due to immunoprotection, since the experiments were conducted in either immuno-incompetent animals (NUDE mice) or a model of syngeneic transplantation.…”
Section: Introductionmentioning
confidence: 98%